Decision to buy or rent fixed assets - Santos Jiménez, Néstor (2008)
Organizations require assets to produce and/or sell their products under competitive conditions, generating value for its shareholders, employees and society in general. These assets consist primarily of cash and fixed assets. Fixed assets consisting of buildings, machinery and equipment, over time, become worn and require replacement to ensure product quality. The theme of choice is the choice between buying fixed assets or contract hire provider of these assets. The article presents a methodology for analyzing alternatives to buy or lease assets for the purpose of optimizing the value of a going concern, using criteria of financial profitability and liquidity.